Evaluating Community Perceptions and the Effectiveness of Social Impact Assessment in Sewage Treatment Plant Development - Zaini, Sakawi; Sofia, Ayup; Christopher, Perumal (RSIS International, 2025)
This study investigates the awareness, perceptions, and level of public acceptability regarding the proposed upgrading of the Kuala Sawah Sewage Treatment Plant (STP). A structured survey was conducted to assess the community’s knowledge of the project, perceived socio-economic, environmental, and cultural impacts, as well as their general level of support or opposition. The findings reveal a high level of community support, despite low awareness, with the majority perceiving the project as beneficial in terms of employment, infrastructure improvement, and environmental enhancement. The study emphasizes the importance of effective communication strategies and stakeholder engagement in public infrastructure projects and evaluates the effectiveness of the Social Impact Assessment (SIA) process in this context.